Smartphone Overuse and Relationship Dissatisfaction: The Mediating Role of Fear of Missing Out (FoMO) - Mehdiabadi, Parichehr; Hooshmandi, Roodi; Yang, Jiantang; Karakus, Mehmet (Journal of Assessment and Research in Applied Counseling (JARAC), 2025)
Objective:  The objective of this study was to investigate the relationship between smartphone overuse and relationship dissatisfaction among young adults, with a specific focus on examining the mediating role of fear of missing out (FoMO).Methods and Materials: A descriptive correlational design was employed, involving a sample of 400 young adults recruited from Manchester, United Kingdom. The sample size was determined based on the Morgan and Krejcie table to ensure adequate statistical power. Participants completed three validated instruments: the Smartphone Addiction Scale–Short Version (SAS-SV) for smartphone overuse, the Fear of Missing Out Scale (FoMOS) for FoMO, and the Couples Satisfaction Index (CSI-16) for relationship dissatisfaction. Data analysis was conducted using SPSS-27 for descriptive statistics and Pearson correlation analyses, while Structural Equation Modeling (SEM) was performed with AMOS-21 to test the hypothesized mediational model.Findings: Pearson correlations revealed significant positive associations between smartphone overuse, FoMO, and relationship dissatisfaction (all p < .001). Model fit indices indicated acceptable fit (χ²/df = 2.01, CFI = .96, TLI = .95, RMSEA = .051), supporting the robustness of the mediational model. Smartphone overuse significantly predicted FoMO (β = .48, p < .001) and relationship dissatisfaction both directly (β = .29, p < .001) and indirectly through FoMO (β = .17, p = .002). The total effect of smartphone overuse on relationship dissatisfaction was β = .46 (p < .001), confirming the mediating role of FoMO in this relationship.Conclusion: The findings underscore the need for interventions that address not only digital dependency but also the psychological mechanisms, such as FoMO, that intensify relational strain in the digital age.